Extramedullary plasmacytoma of the larynx - Pinto, José Antônio; Sônego, Thiago Branco; Artico, Marina Spadari; Leal, Carolina de Farias Aires; Bellotto, Silvana (International Archives of Otorhinolaryngology, 2012)
Introduction: The extramedullary plasmocytoma is one of the localized forms of malignancy of the plasma cells, which has multiple myeloma main diagnosis. Its main site to the head and neck, but with a rare presentation in the larynx.Objective: To describe a case of extramedullary plasmocytoma of the larynx, with literature review.Case Report: Patient female, 49, referring to intermittent dysphonia for 01 years with progressive worsening associated with vocal fatigue and vocal effort, with reddish lesion, smooth edges fold left ventricular endoscopy. Being subjected to excisional biopsy diagnosed with extramedullary histopathological plasmocytoma.Conclusion: Extramedullary Plasmocytoma must be considered in the differential diagnosis of rare tumors of the larynx. It is essential after the diagnosis of multiple myeloma research and a “follow up” appropriate.
Keywords: plasmocytoma; larynx; laryngeal diseases